Role of Fas/Fas Ligand Pathway in a Sample of Iraqi Diabetic Foot Patients - Hussian , Sabah Khorsheed; Al-Karawi , Isam Noori; Sahab , Khalid Shalaan (Diyala Journal of Medicine, 2019)
Background: Diabetic foot (DF) is one of diabetes mellitus (DM) complication, it is delayed wound healing and may end with amputation of limbs. Involvement of Fas/Fas ligand (FasL) pathway in the pathogenesis of diabetic complications has been proposed. Apoptosis via Fas/FasL interactions has been proposed to be a major T-cell-mediated effector mechanism in autoimmune diabetes. Objectives: To investigate Fas/Fas Ligand, in patients with type 2 diabetes who have diabetic foot ulcerations. Methods: sFas, sFasL and high sensetive-CRP were measured with the ELISA method in thirty(30) normal controls (group I), twenty five patients with type 2 DM with no diabetic foot (group II) and twenty five diabetic foot patients with type 2 DM (group III). Besides, serum glucose (Fasting), lipid profile (total cholesterol, triacylglycerol, HDL, LDL and VLDL), body mass index, Waist circumstance and age were determined.The study was carried out in National center of diabetes, Al-Mustansirya University, Baghdad, Iraq. Results: The patients with diabetic foot lesions were found to be poorly controlled and had significantly higher levels of fasting blood glucose (FBG) (p<0.05, p<0.001) compared to patients without diabetic foot lesions and healthy control groups.Also the patients with diabetic foot lesions were found to be significantly have higher levels of sFas and FasL compared to patients without diabetic foot lesions and healthy control groups (p<0.001, p<0.05) respectively. Serum levels of total cholesterol, triacylglycerol, LDL and vLDL were significantly higher (p<0.05) in diabetic patients (with and without foot ulceration) in comparison with healthy normal control. While HDL-c level was lower in both groups than in the control group, it was reach statistical significance.There are no significant different in lipid profile between diabetic foot patients and without diabetic foot patients. sFas serum levels were significantly increased in both diabetic groups compared with normal controls (12.2±2.18 ,10.55±2.57 ng/ml Vs 5.91±3.1 ng/ml, p<0.001), but the levels were significantly higher in patients with diabetic foot when compared with those without diabetic foot patients (p<0.05). sFasL serum levels were also increase in both diabetic patients as compared with normal controls(2.55+1.06, 1.75+0.62 ng/ml Vs 1.59+0.32 ng/ml,p<0.05), but the levels were higher in diabetic foot patients than those without diabetic foot patients. The duration of DM of patients were with >10 yrs, age > 58 yrs, and BMI >25 Kg/m2. A significant positive correlation was observed between sFas and (sFasLand hs-CRP) in diabetic foot patients. Also the same with sFas and (FBG, and lipids). Conclusion: We conclude that the apoptotic pathway in the development of diabetic foot increases by means of the Fas/FasL,and the development of new treatment against apoptosis may play an important role in the management of diabetic foot lesions